Metaphorologie des Kinos: Sprachbilder und Intermedialität im literarischen Kinodiskurs der Klassischen Moderne - Yanagibashi, Daisuke (transcript, 2020)
As a contradictory predication, a metaphor proves to be an extremely suitable means of precisely staging the ambiguity of the film experience on a textual level.